PENGARUH EDUKASI TENTANG KOMUNIKASI PADA PASIEN TUNARUNGU TERHADAP PENGETAHUAN PERAWAT - Shadiyanto, Aldy (Tanjungpura Journal of Nursing Practice and Education, 2021)
Background: The inadequacy of information about deaf communication to nurses in providing nursing at the hospital so that services to Deaf patients are not optimal. Audiovisual media an education method is one the intervention that can overcome the lack of nurses' knowledge on deaf patients' way of communication. Method : Quantitative Quasy Experimental Study Pre and Post Test with nonequivalent control group design. The sampling technique was nonprobability sampling with a convenience sampling / accidental sampling method, given by 36 respondents divided into an intervention group and control group. The instrument used was an online questionnaire within 13 questions, for statistical results using the Paired T-Test and Independent T-Test with a P-value 0.05. Result :Knowledge of Nurse intervention group before and after education are P = 0,000, meanwhile for the control group are P = 0.402. The Independent T Test on the post test resulting in both groups showed a value of P = 0.001(OR = 17.0, 95% CI = 1.85-156.27). Conclusion : There is a difference in the knowledge of Nurse after being given education about communication to deaf patients, both for intervention and control groups. Increased knowledge of the subject is expected to provide better services to deaf patients.Keywords : Deaf Communication, Deaf, Nurse Knowledge